THE PREVALENCE OF NON-INFECTIOUS DISEASES RISK FACTORS IN RUSSIAN POPULATION IN 2012-2013 YEARS. THE RESULTS OF ECVD-RF - G. A. Muromtseva; A. V. Kontsevaya; V. V. Konstantinov; G. V. Artamonova; T. M. Gatagonova; D. V. Duplyakov; A. Yu. Efanov; Yu. V. Zhernakova; V. A. Il’in; A. O. Konradi; R. A. Libis; E. V. Minakov; et al. (Кардиоваскулярная терапия и профилактика, 2014)
In the frame of Multicenter observational study ECVD-RF (Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation) by the unique protocol the investigation of representative selections of adult population at the age of 25-64 y.o. of 11 regions RF (n=18305, including males, n=6919 and females n=11386): Volgograd, Vologda, Voronezh, Ivanovo, Kemerovo, Orenburg, Samara, Tomsk, Tyumen, Saint-Petersburg and Northern Osetia-Alania. The prevalence of the following risk factors (RF) of cardiovascular diseases is evaluated: high blood pressure — 33,8%, obesity — 29,7%, high total cholesterol — 57,6%, high glucose level or diabetes — 4,6%, smoking (tobacco consumption) — 25,7%, insufficient (low) level of physical activity — 38,8%, excessive salt consumption — 49,9% and insufficient vegetables and fruits consumption — 41,9%. Gender differences and an increase with the age of the parameters mentioned are described.The absence of a epidemiologic monitoring system at the Federal level leads to an impossibility of clear conclusions on the RF dynamics in Russian population. While comparing the ECVD-RF study with previous epidemiological studies we can just cautiously suppose the existence in 21st age of negative dynamics of one RF (obesity, dyslipidemia) and positive dynamics of the others (smoking).